Interlink between physiological and biomechanical changes in the swim-to-cycle transition in triathlon events: a narrative review - Ambrosini, L.; Presta, V.; Galli, D.; Mirandola, P.; Vitale, M.; Gobbi, G.; Condello, G. (Sports Medicine - Open, 2022)
Triathlon is a multisport composed of swim, cycle, and run segments and two transition periods. The swim-to-cycle transition is considered a critical period for the change in body position and the modifications in physiological (heart rate, VO2, lactate) and biomechanical parameters (cycling power and cadence, swimming stroke rate). Therefore, the aim of this review was to summarize the current evidence regarding the physiological and biomechanical changes and their interlink during the swim-to-cycle transition hinting at practical recommendations for coaches and athletes. The influence of the swim segment on cycle one is more evident for short-distance events. Greater modifications occur in athletes of lower level. The modulation of intensity during the swim segment affects the changes in the physiological parameters (heart rate, blood lactate, core temperature), with a concomitant influence on cycling gross efficiency. However, gross efficiency could be preserved by wearing a wetsuit or by swimming in a drafting position. A higher swim leg frequency during the last meters of the segment induces a higher cadence during the cycle segment. Training should be directed to the maintenance of a swimming intensity around 80-90% of a previous maximal swim test and with the use of a positive pacing strategy. When athletes are intended to train consecutively only swim and cycle segments, for an optimal muscle activation during cycling, triathletes could adopt a lower cadence (about 60-70% of their typical cadence), although an optimal pedaling cadence depends on the level and type of athlete. Future research should be focused on the combined measurements of physiological and biomechanical parameters using an intervention study design to evaluate training adaptations on swim kick rate and their effects on cycling performance. Coaches and athletes could benefit from the understanding of the physiological and biomechanical changes occurring during the swim-to-cycle transition to optimize the overall triathlon performance.